DO AQUATIC ACTIVITIES BOOST SOCIAL SKILLS FOR CHILDREN WITH AUTISM SPECTRUM DISORDERS? - Maria BELLA (National Centre for Policy and Evaluation in Education, 2019)
This paper provides a number of aquatic programmes, and critically analyzes methods and techniques used to develop social skills in young children with Autism Spectrum Disorders (ASD). Social skills are interpreted through a ToM theory lens, emphasizing interactions, such as understanding, explaining, predicting, and manipulating the behavior of themselves and others. Based on these elements, the purpose of this review is to study the role of adapted group aquatic programmes and its effect on children with ASD to understand the concept of peers and learning the benefits of two important social skills, teamwork, and relationships. An online search through ProQuest and First Search resulted in seven studies of diverse methodologies. All these studies support the value of these programmes as a means of social skills' development. Qualitative as well as quantitative data which included, checklists, interviews, and tests, indicated these programmes benefit ASD children's' social skills, such as cooperation, communication and increase in self-esteem. Findings suggested that children with ASD have opportunities to make new friends, feel more comfortable in a group and reduce anxiety through swimming. These relationships can continue, as they discover other common interests. More longitudinal studies are needed to develop aquatic activities as an extracurricular activity and the planning process to achieve the intended outcomes. By synchronizing theory with sports activities and teamwork, children with ASD can feel a deep sense of accomplishment upon achievement.